Influence of lattice strain on Fe3O4@carbon catalyst for the destruction of organic dye in polluted water using a combined adsorption and Fenton process. Issue 64 (26th October 2020) - Santhanaraj, D.; Joseph, N. Ricky; Ramkumar, V.; Selvamani, A.; Bincy, I. P.; Rajakumar, K.
Abstract : The activity of the catalyst was directly correlated using lattice strain calculations, as derived from the W–H model. Abstract : In this study, 8, 25 and 50 wt% Fe3 O4 @activated carbon (AC) catalysts were prepared by simple coprecipitation method. The efficiency of the catalysts for the advanced Fenton's oxidation process using methylene blue (MB) as a model substrate was tested. Both modified and unmodified activated carbon catalysts exhibited similar activity towards the Fenton's oxidation process. Therefore, it is difficult to identify the role of the catalyst in this dye removal process. Hence, we proposed a new methodology to remove the MB by adopting the adsorption process initially, followed by the Fenton's oxidation process. The proposed process significantly improved the methylene blue decomposition reaction over the 25 wt% Fe3 O4 @AC catalyst. However, this trend was not seen in pure activated carbon and Fe3 O4 @AC (8 and 50 wt%) catalysts due to the instability of the material in the oxidizing medium. The possible reason for the deactivation of the catalysts was evaluated from lattice strain calculations, as derived from the modified W–H models (Uniform Deformational Model (UDM), Uniform Stress Deformation Model (USDM) and Uniform Deformation Energy Density Model (UDEDM)). These results provided a quantitative relationship between the experimentally calculated lattice strain values and Fenton's catalytic activity. Furthermore, the optimized strain value and crystalite size of Fe3 O4 on the activated carbon matrix are responsible for the high catalytic activity.